Optimization, fabrication and characterization of a binary subwavelength cylindrical terahertz lens - S.I. Kharitonov; V.S. Pavelyev; N.L. Kazanskiy; Y.S. Strelkov; K.N. Tukmakov; A.S. Reshetnikov; S.V. Ganchevskaya; V.V. Gerasimov; B.A. Knyazev (Компьютерная оптика, 2023)
A problem of optimizing the subwavelength microrelief of a binary cylindrical transmissive diffractive lens (DL) with a 300-mm focal length for a wavelength of λ=141 μm was considered. High-resistivity silicon was chosen as the DL substrate material. The angle of incidence of the illuminating beam was taken to be π/6. The optimization parameters were the height of the DL profile and the fill factor of the groove. The main goal of optimizing the design was to increase the diffraction efficiency of the lens. The DL diffraction efficiency was calculated using a Fourier mod method. The DL was fabricated by plasma-chemical etching (Bosch process) of the surface of a silicon substrate. The diffraction efficiency of the calculated lens was estimated to be 70%. However, a full-scale experiment showed the real efficiency to be much lower. These differences are related to both errors in the manufacturing process of the DL and non-ideal thickness parameters of the silicon wafers.